2011
DOI: 10.1080/02626667.2010.538396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature change on water discharge, and sediment and nutrient loading in the lower Pearl River basin based on SWAT modelling

Abstract: The impact of climate change on hydrological processes and nutrient input is one of the major uncertainties in projecting future global warming. The Soil and Water Assessment Tool (SWAT) model is applied to simulate the effects of temperature on the hydrology and sediment and nutrient load in the lower Pearl River Basin, South China. Calibration and validation results for SWAT showed that the Yamen estuary is appropriate for simulating the impacts of temperature change on both hydrological processes and nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 56 publications
2
37
0
Order By: Relevance
“…Representation of monthly average flow was also satisfactory (ENS: 0.80-0.91), where ENS values in other Chinese studies have been reported to range between 0.63 and 0.93 for the monthly average flow (e.g. Li et al 2011). During calibration of hydrology several parameters were changed specifically for each soil layer and land use type, but also globally (Table 8).…”
Section: Management Options For Improving Reservoir Water Qualitymentioning
confidence: 84%
See 1 more Smart Citation
“…Representation of monthly average flow was also satisfactory (ENS: 0.80-0.91), where ENS values in other Chinese studies have been reported to range between 0.63 and 0.93 for the monthly average flow (e.g. Li et al 2011). During calibration of hydrology several parameters were changed specifically for each soil layer and land use type, but also globally (Table 8).…”
Section: Management Options For Improving Reservoir Water Qualitymentioning
confidence: 84%
“…SWAT has been used in several studies in China to assess impacts of climate changes, land-cover changes and land use (e.g. Ouyang et al 2008;Li et al 2011) on hydrology and, to some extent, on nutrient export. However, to incorporate the connectivity between watersheds and reservoirs, we expanded the ordinary SWAT-watershed approach by coupling it with a simple, but widely used, empirical equation to estimate total phosphorus (TP) concentrations in the reservoir (Vollenweider and Kerekes 1982) for use as a proxy of trophic status.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters FL, SD, IN and TP decreased as temperature rose, while N3 increased slightly. However, the situation was different for the DWR, where FL changed very slightly, while SD increased strongly or decreased slightly, respectively, when temperature rose or dropped (Li et al 2011). The parameter IN showed a significant increasing tendency under climate warming scenarios (Li et al 2011).…”
Section: Different Response Of Two Subtropical Watersheds To Temperaturementioning
confidence: 92%
“…Previous research by the authors (Li et al 2011) revealed the effect of temperature change on water discharge and nutrient loading in the downstream area of the Xijiang River (Downstream of West River, DWR). Because the regional patterns of change in hydrological processes under warming were very complex, in this study we compared the UER with the DWR to check whether temperature change had a similar effect on two watersheds in close proximity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation